Sex‐specific associations between cardiovascular risk factors and physical function: the Gambian Bone and Muscle Ageing Study. Issue 1 (8th November 2022) - Zengin, Ayse; Ó Breasail, Mícheál; Parsons, Camille M.; Jarjou, Landing M.; Janha, Ramatoulie E.; Jobe, Modou; Prentice, Ann; Cooper, Cyrus; Ebeling, Peter R.; Ward, Kate A.
Abstract: Background: In Sub‐Saharan Africa, the prevalence of obesity, cardiovascular disease (CVD) and impaired physical function are increasing due to rapid urbanization. We investigated sex differences in associations between cardiac workload, arterial stiffness, peripheral vascular calcification (PVC) and physical function in Gambian adults. Methods: A total of 488 Gambians aged 40–75+ years were recruited (men: 239; and women: 249). Supine blood pressure and heart rate were measured to calculate rate pressure product and pulse pressure. Presence of PVC was determined from tibia peripheral quantitative computed tomography scans. Physical function was assessed by chair rise test (CRT), single two‐legged jump (s2LJ) and hand grip strength (HGS). Body composition was measured by dual‐energy x‐ray absorptiometry; body size corrections were used to calculate fat mass index (FMI) and appendicular lean mass index (ALMI). Estimated glomerular filtration rate (eGFR) was measured from fasting blood samples. The relationship between rate pressure product, pulse pressure or presence of PVC (independent variable) with physical function parameters (dependent variable) was tested using linear regression. Sex‐interactions were tested (p‐int) adjusting for age, eGFR and ALMI/FMI. Results were expressed as mean differences between men and women with 95% confidence intervals. Mediation analyses used ALMI/FMI as mediator. Results: Women weighed less (54.7 kg ± 10.3 vs. 59.9 kg ± 10.3) and were shorter (157.8 cm ± 6.0 vs. 169.2 cm ± 7.0) compared with men (both P < 0.0001). Women had higher FMI (6.8 kg/m 2 ± 2.9 vs. 2.9 kg/m 2 ± 2.0, P < 0.0001) and eGFR (263.7 mL/min/1.73 m 2 ± 133.1 vs. 237.6 mL/min/1.73 m 2 ± 134.6), but lower ALMI (6.2 kg/m 2 ± 0.7 vs. 8.02 kg/m 2 ± 1.0, P < 0.0001) compared with men. There were significant mean differences between men and women in rate pressure product and s2LJ power (−1.08 [−1.21, −0.95]) and force (−0.57 [−0.63, −0.51]), only after adjusting for age, eGFR and FMI. There were significant mean differences in the associations between pulse pressure and CRT power (−0.28 [−0.31, −0.25]), s2LJ power (−1.07 [−1.20, −0.93]) and HGS (−11.94 [−13.35, −10.54]); these differences were greater after adjusting for age, eGFR and FMI, than ALMI. There were similar differences in the associations between PVC and physical function parameters. In men, FMI mediated the association between rate pressuree product and CRT power ( P = 0.002), s2LJ force ( P < 0.001) and s2LJ power ( P = 0.001). ALMI did not mediate associations for either men or women. Conclusions: Multiple risk factors for CVD were associated with poorer physical function in men and were mediated by FMI. There is a need to identify strategies to slow/prevent the rising CVD burden and poor physical function in Sub‐Saharan Africa.